DNPM actions on the implementation of law 12.334/2010: from the ordinances and inspections to the SIGBM - Leite,Eriberto Nascimento (2019)
Abstract As defined in PNSB - Law 12.334/2010 (Brasil, 2010), the DNPM, which manages the Brazilian mineral resources, is also responsible for overseeing the safety management of tailings dams in the country. The purpose of this article is to present the actions carried out in this context by the Department since the enactment of the Law in 2010, such as: elaboration of infra-legal regulatory instruments, training of civil servants, inspection actions throughout the country, seminars and lectures at mining companies and the organized civil society in general, among others, with the primary purpose of monitoring the implementation of the law instruments by mining companies, such as PSB and PAEBM, in order to avoid / mitigate accidents related to these structures.